2018 IEEE 88th Vehicular Technology Conference (VTC-Fall) 2018
DOI: 10.1109/vtcfall.2018.8690995
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Environment Perception Approach for Vehicular Ad Hoc Networks

Abstract: In this paper, we focus on vehicular safety applications based on the Dedicated Short Range Communication (DSRC) standard. We propose a new mechanism to alleviate channel congestion by reducing the beacons load while maintaining an accurate awareness level. Our scheme is based on the collective perception concept which consists in sharing perceived status information collected by vehicles equipped with different types of sensors (radars, lidars, cameras, etc.). To achieve our goal, we propose two main schemes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In this paper, we analyzed the utilization and benefits of the vehicle's embedded sensors to enhance car perception and improve cooperative communication efficiency. To this purpose, we implemented the Collaborative Environment Perception Approach for vehicular safety applications proposed by [1] and analyze its performance and behavior in congested urban traffic. In this ECAM (Extended Cooperative Awareness Message) mechanism, vehicles share information of their neighboring vehicles through a collaborative beaconing scheme to reduce congestion on the communication channel collected by their various type of sensors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we analyzed the utilization and benefits of the vehicle's embedded sensors to enhance car perception and improve cooperative communication efficiency. To this purpose, we implemented the Collaborative Environment Perception Approach for vehicular safety applications proposed by [1] and analyze its performance and behavior in congested urban traffic. In this ECAM (Extended Cooperative Awareness Message) mechanism, vehicles share information of their neighboring vehicles through a collaborative beaconing scheme to reduce congestion on the communication channel collected by their various type of sensors.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that a cooperative approach that uses vehicles' embedded sensors does not degrade these parameters while increasing the communication range and awareness of the vehicles while reducing the channel load. [1] enhances the classical CAM scheme and provides a collective perception approach by sharing the information collected from embedded sensors among connected vehicles. The objective is to take advantage of some safety features using sensors integrated to recent vehicles, such as acoustic sensors, cameras, radars, lidars, etc.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, channel overloading being one major issue with CPM dissemination, it has been shown that controlling CPM content can have a positive impact on channel usage [24,31]. In [32], the authors proposed to assess channel congestion to adapt object inclusion policies.…”
Section: Related Workmentioning
confidence: 99%